2003. Routine Use of Anaerobic Blood Cultures at Thammasat University Hospital, Thailand. (26th November 2018) - Suwantarat, Nuntra; Apisarnthanarak, Anucha; Carroll, Karen C
Abstract: Background: There are limited data on routine use of anaerobic blood cultures and the prevalence of patients with anaerobic bacteremia in Thailand. Methods: Thammasat University Hospital is a 650-bed university hospital located in central Thailand. We implemented routine blood culture work up for adults using paired aerobic/anaerobic bottles using the BACTEC FX system (BD Diagnostics) as a standard practice. Gram stain and inoculation of positive blood cultures on aerobic and anaerobic culture media were performed and maintained in anaerobic conditions by the Anoxomat™ system (Mart Microbiology). Vitek2 system (BioMerieux) was used for bacterial identification. Data on positive blood cultures, bacterial identification, and time to positivity (TTP) between aerobic and anaerobic bottles were compared. Characteristics of patients with bacteremia were reviewed. Results: During December 2016–October 2017, 323 blood culture sets were processed (one BACTEC anaerobic Plus bottle and two aerobic bottles). Majority of samples received were from patients hospitalized in an intensive care unit (surgical ICU 28% and medical ICU 25%) followed by general medical unit (19%) and surgical unit (16%). There were 21 positive cultures from anaerobic bottles (21/323, 6.5%) vs. 30 positive cultures from aerobic bottle (30/646, 4.6%) ( P = 0.3). Bacteria isolated from anaerobic bottles included Staphylococcus aureus ( n = 8), coagulase-negative staphylococci ( n = 3), viridans group streptococci ( n = 1), Klebsiella pneumoniae ( n = 8), and Escherichia coli ( n = 1). Positivity rate of Gram-positive bacteria (GP) from anaerobic bottle was slightly higher than the rate of GP from aerobic bottle (12/203, 3.1% vs. 12/646, 1.9%; P = 0.08) There was no isolation of anaerobic bacteria. TTP from anaerobic bottles (mean of 15.6 hours, range 11–26 hours) was significantly faster than TTP from aerobic bottles (mean of 49.5 hours, range 13–100 hours) ( P < 0.001). The majority of the positive samples were from patients hospitalized in an ICU (16/21, 76.2%), especially in a surgical ICU (13/21, 61.9%). Conclusion: Our population had a low prevalence of anaerobic bacteremia. The anaerobic bottle significantly decreased the TTP compared with an aerobic bottle. The cost-effectiveness of routinely including an anaerobic blood culture bottle needs further study. Disclosures: All authors: No reported disclosures.